POVERTY IN DAERAH ISTIMEWA YOGYAKARTA (DIY): POLICIES AND EFFORTS TO SOLVE IT (DATA YEAR OF 2010-2016) - Muhammad Findi Alexandi; Edi Victara Tinambunan (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2019)
This research analyze some factors that influence of poverty level and some formulation policies to solve poverty in Daerah Istimewa Yogyakarta (DIY). By 2017 Province of DIY becomes the highest poverty rate in Java Island. The percentage of poor people in Province of DIY is also above the average percentage level of poverty in Indonesia. Therefore our research is conducted on what are the factors of affect poverty and what can be implemented to solve it. This research used panel data and calculated with Ms Excel and software of Eviews 9. The range period of this research from year of 2010 to 2016 with five districts/cities in Province of DIY. The result of the estimation in this research showed that economic growth has positively affect to poverty, while the health facilities, educational facilities and the number of labor agricultural sector have negatively affect to poverty level in Province of DIY.JEL Classification: I30, I32, I38Keywords: Economic Growth, Educational Facilities, Health Facilities, Labor Of Agricultural Sector, Poverty